Designing a Policy-Making Model for Biomass Energy Development Training in the Agricultural Supply Chain Sector - Tahereh Pourelmi; Seyed Mohammad Shobeiri; Enayatollah Yazdanpanah; Gholam Reza Bakhshi Khaniki; Mahdieh Rezaei (Discrete Dynamics in Nature and Society)
This basic-applied and hybrid survey aimed to design and validate a policy-making model for biomass energy development training in the agricultural supply chain sector. Creating a supply chain for basic agricultural products by including a wide range of agricultural subsectors from the supply of required production inputs to the final consumer’s access to the goods will lead to an increase in the productivity of the agricultural sector as well as the upstream and downstream industries related to it. Therefore, considering the importance of creating an optimal supply chain for various agricultural products, in this study, the situation of the supply chain of agricultural products in the country has been examined. Considering that the lack of appropriate policies regarding the management of the supply chain of agricultural products can lead to the inefficiency of the supply chain of agricultural products in various stages including supply of inputs, production and distribution, and marketing of products, it is suggested that planning and related policies should be implemented in order to improve the infrastructure that leads to increasing the efficiency of some logistics subsystems such as transportation, warehousing, communication, and information systems. Purposive sampling was used in the qualitative part, and stratified random sampling was utilized in the quantitative part. The data were collected by reviewing resources and interviewing ten experts, who were mainly policy-making managers of biomass energy development training and academic researchers. The interviews continued until reaching theoretical saturation, and the samples of the quantitative part included 384 members of the environmental and agricultural Jihad employees, who were selected based on Cochran’s formula. The effective components of the education policy of biomass energy development and their factors were identified by the exploratory method and evaluated through descriptive-survey research. The validity and reliability of the components were examined, and Cronbach’s alpha of all components was higher than 0.7. The essential components of the effective factors were measured in the education policy of biomass energy development in the agricultural sector. The model validity was verified through the structural equation method, and the selection of concepts, dimensions, and indicators was highly accurate and could provide a suitable framework for developing a policy perspective document for biomass energy education. According to the coding results, the development and acceptance of biomass energy systems by the Ministry of Agriculture Jihad and Environment in the country is unsuitable and sustainable, considering the passage of more than a decade of designing and implementing plans. According to experts, some farmers implement this method in their fields for one or two years and return to traditional methods after accepting this technology. The main achievements are as a core category or phenomenon conditions to casual conditions path with coefficient 0.916 is significant. Strategies to the core category or phenomenon conditions’ path with a coefficient of 0.051 are significant. Strategies to contextual conditions’ path with coefficients 1.231 are significant. Strategies for intervening condition path with coefficients 2.235 are significant. Consequences to strategies’ path with coefficients 0.807 are significant. Therefore, the development of biomass energy is an inevitable necessity, considering the erosion and reduction of soil organic matter, increasing energy costs, and other factors.